Analysis of the microstructure transformation (wel formation) in pearlitic steel used in relevant engineering wear systems. - Pereira Agudelo, Juan Ignacio (2018)
In this thesis, the behavior of pearlitic steel was characterized under controlled wear conditions in the laboratory and service conditions in two ore mining stages, comminution and transportation. The thesis consists in three experimental chapters, divided according to the tribosystems analyzed. On all the chapters Electro Microscopy techniques for the microstructural analysis were employed. Scanning Electron Microscopy (SEM), Focused Ion Beam (FIB-SEM), Electron Backscatter Diffraction (EBSD) and Transmission Electron Microscopy (TEM) were used. The first experimental chapter shows the analysis of the pearlite under abrasive wear with loose abrasive particles in multi-events conditions. The sample was taken from Semi-Autogenous Grinding mills (SAG) and experimental simulation was carried out in laboratory using the Dry Sand Rubber Wheel Abrasion Test (DSRW). The results show a polycrystalline layer formation in both cases, characterized by ultra-fine grains of ferrite in the layer closer to the surface. It was also concluded that the DSRW can simulate the wear produced on field (superficial and microstructural features) in conditions of higher normal load than recommended by the ASTM Standard G65. The second experimental chapter explores the characterization of the microstructure after the indenter pass in scratch test using two conditions of normal load applied and five sequences of scratch. The microstructural analysis shows the formation of two subsuperficial layers identified by the level of the microstructural alterations. In the subsuperficial layer (close to the surface), the formation of new ultra-fine grains of ferrite was observed. A second layer was observed deeper in the sample and denominated as layer of the microstructure transition, characterized by the combination of deformed (reduction of the interlamellar spacing) and pearlite colonies not affected plastically by the mechanical loading. On this layer, the crystallographic texture in RD // in samples tested at 4 N (normal load) and one-pass scratch was determined. Later, on this chapter, the microstructure in a ground rail (industrial procedure characterized as a multi-event scratch test) was analyzed. Two grinding conditions were used for the analysis with variation of the grinding linear speed and load on the grinding stones (discs). The combination of low grinding speed and high load promotes a higher deformed layer formation beneath the patch zone and low randomized orientation of the pearlite colonies. Finally, in the third experimental chapter, the pearlitic characterization was concluded with the study of samples of railway wheel and rail under wear in service and Rolling Contact Fatigue (RCF) in laboratory. The laboratorial simulation was carried out using the twin-disc rolling contact tribometer with a variation of number of cycles. The characterization of railway wheel shows that the WEL is characterized by levels of breaking and aligned cementite and zones with dissolution of the carbon atom in the ferrite to form the supersaturated carbon ferrite. The polycrystalline ferrite formation (ultra-fine grains) in the sub-superficial layer and it was identified a preferential orientation of RD // in the layer of microstructural transition. The results of the laboratory test show surface crack nucleation and propagation at low angle in the more severe deformed layer. The microstructure of the layer consists in polycrystalline ferrite and the cementite dissolution.